2021
DOI: 10.1088/2058-6272/abe3e1
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of OH radicals produced in a DC glow discharge by laser-induced fluorescence spectrometry

Abstract: In this paper the OH radicals produced by a needle–plate negative DC discharge in water vapor, N2 + H2O mixture gas and He + H2O mixture gas are investigated by a laser-induced fluorescence (LIF) system. With a ballast resistor in the circuit, the discharge current is limited and the discharges remain in glow. The OH rotation temperature is obtained from fluorescence rotational branch fitting, and is about 350 K in pure water vapor. The effects of the discharge current and gas pressure on the production and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Meanwhile, the amounts and kinds of the active species in plasmas are also critical important in many applications because those species participate physicochemical processes [23]. Usually, to improve the uniformity of atmospheric DBDs, the discharges need operate in inert gases, such as Ar and He, and there is lack of active and functional radicals for plasma-chemical processing.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the amounts and kinds of the active species in plasmas are also critical important in many applications because those species participate physicochemical processes [23]. Usually, to improve the uniformity of atmospheric DBDs, the discharges need operate in inert gases, such as Ar and He, and there is lack of active and functional radicals for plasma-chemical processing.…”
Section: Introductionmentioning
confidence: 99%
“…31 Plasma generation and its role are performed in a variety of ways (Fig. 1b), 40 including dielectric barrier discharge (DBD), 41 glow discharge, 42 microwave discharge, 43 radio frequency discharge, 44 spark discharge, 45 corona discharge, 46 etc . Due to the different external control parameters (electrode structure, power supply, and type of working gas), the plasma characteristics generated by gas discharge are also different.…”
Section: Plasma Materials Preparation Technologymentioning
confidence: 99%
“…to provide reactive species [10,11]. Among these gases, H 2 O in the vapor phase is an important reactive gas that adds to the gas mixture to produce hydroxyl radicals (OH), atomic oxygen and hydrogen, which plays a key role in the physicochemical processes [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the densities of electrons and active species in the configuration of two-pin electrodes are much higher than those in other electrode configurations. For example, in a plasma jet with a two annular electrode configuration, Yue et al reported that the OH density was measured up to ~1× 10 20 m −3 for discharges driven by a voltage of 5 kV [12]. However, with regard to pin-to-pin discharges, Verreycken et al reported that the OH density is at the level of 10 22 m −3 under similar applied-voltage conditions [16].…”
Section: Introductionmentioning
confidence: 99%